Comparative And Competitive Advantage Agribusiness Of Jawa Brebes Cattle (Jabres) In Brebes Regency - Suci Nur Utami; M Syaifulloh (Badan Penerbitan Fakultas Pertanian (BPFP), Universitas Bengkulu, 2019)
The development of Jabres cattle is very important to increase the population of Jabres cattle in Brebes. There needs to be a good developmentstrategy so that Jabres cattle can have a higher competitiveness. The purpose of this research is to know the level of comparative and competitive advantages agribusiness of Jabres cattle known from the value of Domestic Resources Cost Ratio (DRCR) and Private Cost Ratio (PCR), and to determine the priorities of the development strategy Agribusiness of Jabres cattle uses the method of Analytical Hierarchy Process (AHP) with Expert Choice program. The results show that the DRCR value is 0.97 and PCR is worth 0.96, it indicates that Cow Jabres has a comparative and competitive advantage so that it can be competitiveness at the national level. Based on the Anaytical Hierarchy Process analysis that has been done, obtained the results that the most important strategy priority used to develop the agribusiness of Jabres cattle in Brebes is by increased effectiveness in livestock maintenance.